Detailed kinetic study on methane/diesel RCCI combustion. (August 2021) - Heidarabadi, Shadab; Khoshbakhti Saray, Rahim; Neshat, Elaheh
RCCI engines are a novel combustion technology with low pollution and high thermal efficiency. This study aims to identify the reaction pathways in the chemical kinetics mechanism of natural gas and diesel fuel mixture for RCCI combustion. To this end, the engine is simulated using 3D CONVERGE CFD software and then validated by experimental data. In the next step, the chemical reactions are classified with respect to the rate of reactions. Then, the important reactions are identified at various crank positions by considering different numbers of the important reactions and using thermodynamic data and species concentrations obtained from the simulation and the developed code in Fortran. Different reduced mechanisms are developed and compared with the main mechanism with respect to the critical reaction's pathways within two modes of an engine including single and multi-injection cases. Also, the common reactions are compared with the main mechanisms in terms of reaction rate and important species concentration, such as OH, H, H2, O, etc. All the identified reaction pathways indicate the importance of n-heptane reactions. On the other hand, the number of reactions is not important, but rather the type of reactions involved in the mechanism is an important issue. In the main mechanism, the diagram of the chemical reaction pathways in the multi-injection mode is simpler than that of the single-injection mode, indicating the importance of mixing compared to the reaction pathways in the RCCI combustion.